Les temps et les modes des politiques réparatrices - Joëlle Hecker (Temporalités)
This article focuses on the perception of time in the aftermath of mass violence. It demonstrates that reparative measures taken in order to do justice and to establish a dialogue between groups affected by past crimes have an influence on the way time is perceived. In other words, perceived time is modelled by reparations, which are able to rephrase the narrative of the past. More particularly, reparations tend to say something about the responsibility of the perpetrators and the suffering of the victims.To illustrate, the article draws on one case, that of the West German reparations to Israel and at the Claims Conference between 1945 and 1980. The study of this long period of time enables us to analyse changes in the way reparations were done. The 1950s were the years of civil justice, taking the form of financial reparations. In the 1960s, criminal justice took their place. In the 1970s, symbolic acts predominated. Every form of reparation told in its own way the history of the crimes, and hence changed the perception of the past over time.